2019
DOI: 10.1038/s41598-019-39736-8
|View full text |Cite
|
Sign up to set email alerts
|

Printed Microwave Metamaterial-Antenna Circuitries on Nickel Oxide Polymerized Palm Fiber Substrates

Abstract: In this paper, the novelty of exploring the applications of the Iraqi Palm Tree Remnants (IPTR) mixed with Nickel Oxide Nanoparticles (NONP) hosted in Polyethylene (PE), called INP substrates, is utilized by printing metamaterial (MTM) based high gain microwave antennas on them. The proposed INP substrates are mainly created from pressed flexible organic fibers to suite the ink jet printing technologies. The complex relative constitutive parameters are characterized in terms of permittivity (ε) and permeabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 20 publications
1
43
0
Order By: Relevance
“…Multi‐input multi‐output (MIMO) systems are expected to play a major role in the future telecommunication technologies in which the data rate, reliability, quality, and channel capacity maybe increased . Nevertheless, MIMO systems mitigate the effects of the multipath fading . However, the mutual coupling reduction between adjacent antennas separated with less than λ/2 at the operating frequency is one of the most urgent challenges in the modern MIMO designs .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multi‐input multi‐output (MIMO) systems are expected to play a major role in the future telecommunication technologies in which the data rate, reliability, quality, and channel capacity maybe increased . Nevertheless, MIMO systems mitigate the effects of the multipath fading . However, the mutual coupling reduction between adjacent antennas separated with less than λ/2 at the operating frequency is one of the most urgent challenges in the modern MIMO designs .…”
Section: Introductionmentioning
confidence: 99%
“…1 Nevertheless, MIMO systems mitigate the effects of the multipath fading. 2 However, the mutual coupling reduction between adjacent antennas separated with less than λ/2 at the operating frequency is one of the most urgent challenges in the modern MIMO designs. 3 Such coupling reduction in MIMO systems may enhance the corresponding antenna impedance and radiation properties.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is concluded that the effective substrate thickness varies with respect to the incident plane wave, where the substrate thickness at the patch center is less than at the patch edges. Moreover, the defection from cylindrical objects provides different surface propagation from the patch edges …”
Section: T‐stub Gap Effectsmentioning
confidence: 99%
“…In Ahmed and Elwi, MTM‐based microstrip antenna was proposed for wireless sensing. While in Elwi, MTM inclusions were conducted to reduce the effects of absorbed energy by human tissues from portable devices. Later, nano‐scale structures are conducted as another frontier to realize the ability of printing novel antenna circuities for different modern wireless applications In Elwi and Ahmed, the use of nanoparticle conductive ink to fabricate microstrip antennas was convinced.…”
Section: Introductionmentioning
confidence: 99%
“…The full two ports calibration involves the measurements of open, short, and 50 Ω load standards for both ports, followed by a through standard, simply achieved by directly connecting the two supporting cables for each port. In the curing time measurements, the mortar sample is placed (horizontally) in between a pair of lens horn antennas to avoid any diffraction from the edges of the sample [9]. For this, the sample area is chosen to be of size 28 × 28 cm 2 .…”
Section: Measurement Setupmentioning
confidence: 99%